Rapid and High Seed Germination and Large Soil Seed Bank of Senecio aquaticus in Managed Grassland - Matthias Suter; Andreas Lüscher (The Scientific World Journal)
Senecio aquaticus, regionally a Red List species in Europe, has become increasingly abundant in agricultural grassland of medium to high management intensity in Switzerland, Southern Germany, and Austria in recent years, where it is a threat for animal and human health due to its toxicity. In this study, we investigated the seed ecology of S. aquaticus to help protection of the species in relic populations while improving its control when abundant in managed grassland. Germination percentages of fresh ripe seeds of S. aquaticus were on average 68% in 2008, but only 45% in 2010, indicating yearly variation. Germination was generally fast: ten days after the onset of the tests, often more than 45% of all seeds had germinated. When covered with a soil layer of 5 mm, germination was only 16% compared to 63% in full light. Seeds buried in the soil for one and two years showed a germination of 78%, significantly higher than that of fresh ripe seeds, thus suggesting a stimulating effect of cold-wet stratification on germination and long seed survival in the soil. In grasslands with established populations of S. aquaticus, the number of germinable seeds of the species ranged from 361 to 1875 m-2 in topsoil (0–10 cm) with an average of 1139 m-2. The large seed bank and the rapid and high germination of S. aquaticus suggest that allowing seed formation is important for its preservation in relic populations. With respect to agricultural grassland, strategies to control the species should initially target hindering seed production and dispersal.